1989
DOI: 10.1002/ar.1092250104
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of the coiled body and a new inclusion, the “mykaryon”, in the nucleus of the adult rat sertoli cell

Abstract: Random and serial thin sections of the nucleus in adult rat Sertoli cells were examined by electron microscopy. Besides the previously reported nucleoli and heterochromatin masses, the nuclei contain a coiled body and a new structure, the "mykaryon." The coiled body is 835 nm in maximum diameter. It is composed of distinct elements referred to as "coils." They are 32 nm wide on average and resemble the nucleolar pars fibrosa in their intense staining with heavy metal salts and their composition of narrow filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The present findings indicate that the Sertoli cell nuclei show a characteristic distribution of some dense bodies, which closely resemble the coiled body described by Schultz (1989), but they are occasionally attached to the nucleolus. However, the previous study demonstrated that the coiled body exists in situ without structural relationship to the nucleolus.…”
Section: Structure Of Sertoli Cell Nucleus In Thick Sectionssupporting
confidence: 88%
See 3 more Smart Citations
“…The present findings indicate that the Sertoli cell nuclei show a characteristic distribution of some dense bodies, which closely resemble the coiled body described by Schultz (1989), but they are occasionally attached to the nucleolus. However, the previous study demonstrated that the coiled body exists in situ without structural relationship to the nucleolus.…”
Section: Structure Of Sertoli Cell Nucleus In Thick Sectionssupporting
confidence: 88%
“…The formation of the perinucleolar bodies or heterochromatin is still unclear in the present study. Schultz (1989) reported a coiled body and mykaryon in the nucleus of the adult rat Sertoli cell using thin sections. He noted that the coiled body was composed of distinct elements referred to as "coils" and resembled the nucleolar pars fibrosa in their intense staining with heavy metal salts.…”
Section: Structure Of Sertoli Cell Nucleus In Thick Sectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological significance of regulatory changes in 11␤HSD lies in the fact that Leydig cells contain glucocorticoid receptors and are the primary target of glucocorticoid action in the testis (Hales and Payne, 1989;Schultz, 1989;Stalker et al, 1989;Ge et al, 1997b). Because glucocorticoid-induced suppression of testosterone production is mediated by glucocorticoid receptors (Hales andPayne, 1989, Monder et al, 1994b), the intracellular concentration of glucocorticoid within the Leydig cell should determine the magnitude of its effect.…”
Section: Discussionmentioning
confidence: 99%